Voting for direct democracy: Evidence from a unique popular initiative in Bavaria - Felix Arnold; Ronny Freier; Magdalena Pallauf; David Stadelmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
We analyze a constitutional change in the German State of Bavaria where citizens, not politicians, granted themselves more say in politics at the local level through a constitutional initiative at the state level. This institutional setting allows us to focus on revealed preferences for direct democracy and to identify factors which explain this preference. Empirical results suggests support for direct democracy is rather related to dissatisfaction with representative democracy in general than with an elected governing party.
Keywords: D72; H70; 330; Direct democracy; Voting; Initiative; Parties